Dactyloctenium ctenioides (Poaceae: Chloridoideae: Dactylocteniinae): brief note on the taxonomy, distribution and a new record for North America - Landge, Shahid Nawaz; Shinde, Rajendra D.; Mashau, Aluoneswi Caroline; Chandran, Manoj; Thompson, Edward John (Phytotaxa, 2025)
Dactyloctenium ctenioides, previously regarded as the species endemic to East Africa and the West Indian Ocean Islands, has now been identified in a residential landscape in Florida, USA. This study examines its taxonomy, identification, morphological affinities with allied species, and distribution, drawing on specimens housed at BR, K, NHN, P, PIHG, PRE, and US herbaria, majority of which originate from Africa and West Indian Ocean Islands, and relevant global literature. Detailed photographic plates are provided for accurate identification, along with an updated distribution map based on GBIF data. Some possibilities link to its introduction in Florida are discussed. A second-step lectotypification has been conducted to resolve nomenclatural ambiguity, building on the first-step lectotypification inadvertently established in the Flora of East Tropical Africa in 1974. The first key to the global species of Dactyloctenium has been provided to facilitate the precise identification. The authenticated specimen of D. ctenioides housed at the PRE Herbarium, along with the lectotype specimen preserved at the Paris Herbarium (P), are cited as key reference materials for the validation of this species’ identity from Florida, USA.